Association between metabolically healthy overweight/obesity and gallstones in Chinese adults. - Zhang, Junlu; Chen, Liangli; Shen, Keqing; Zhang, Jia; Zhu, Yue; Qiao, Qiaohua; Chen, Liying (Nutrition & Metabolism, 2023)
Background: Metabolic syndrome and obesity are risk factors for gallstones. However, these two factors often occur together, and few studies have focused on the association between metabolically healthy overweight/obesity (MHOW/MHO) and gallstones. We hypothesized that MHO individuals would be associated with the prevalence of gallstones. Methods: This cross-sectional study included 125,668 participants aged 18–80 years at the Health Promotion Center of Run Run Run Shaw Hospital, Zhejiang University School of Medicine during 2017–2019 years. Each participant underwent a comprehensive health checkup. Gallstones were diagnosed by abdominal ultrasonography. Metabolically health was defined as not meeting the diagnostic criteria for metabolic syndrome (MetS). Obesity was measured by BMI. MetS and weight stratification were combined to classify the metabolism-obesity phenotypes. Logistic regression models were used to estimate adjusted odds ratios (ORs) and 95% CIs. Results: Among 125,668 participants, 5486 (4.4%) had gallstones. 21407 (17.0%) were MHOW individuals, and 3322 (2.6%) were MHO individuals. MHOW (OR 1.40; 95%CI: 1.29–1.53) and MHO (OR 1.80; 95%CI: 1.53–2.12) participants were at higher risk of gallstones and had larger and more numerous gallstones than metabolically healthy normal weight participants. Obesity, MetS, premenopausal women and advanced age were significantly associated with the prevalence of gallstones. Conclusions: MHOW/MHO individuals exhibited a higher risk of gallstones. In metabolically healthy individuals, the risk of gallstones increased with increasing BMI. Thus, obesity was associated with the prevalence of gallstones, even in relatively metabolically healthy adults.